Comparison of Agglomerative Hierarchy Methods in Grouping Cities in West Java Based on Gross Regional Domestic Product - Herlinda Nurafwa Sofhya (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
Economic development can be seen through the size of the Gross Regional Domestic Product (GRDP) of a region. Based on the Gini ratio, it can be seen that the economic gap in Â is still quite high and continues to increase from 2019. This cannot be allowed to continue, this gap needs to be reduced. Therefore, the West Java government needs to focus on improving the economy in areas with low economic conditions. One of the main indicators of the economic condition of a region is the amount of GRDP. In this research, cities in West Java are grouped based on GRDP using the agglomerative hierarchy method. The agglomerative hierarchy methods used are single linkage, average linkage and complete linkage methods. Then the three methods are compared based on the standard deviation ratio value. The results of data analysis show that the complete linkage method has a smaller standard deviation ratio value than the single linkage and average linkage methods, which is 0.109016. This means that the best method performance of the three agglomerative hierarchy methods used is the complete linkage method